2019
DOI: 10.1590/1807-1929/agriambi.v23n4p285-290
|View full text |Cite
|
Sign up to set email alerts
|

Biometrics and grain yield of sorghum varieties irrigated with salt water

Abstract: The objective of this study was to identify sorghum varieties that have growth and grain yield potential under saline conditions. The study was conducted in 2016 at a greenhouse of the Embrapa Semiárido, in Petrolina, state of Pernambuco, Brazil (9° 8’ 8.9’’ S, 40° 18’ 33.6’’ W, and altitude of 373 m). A randomized block experimental design, with a 6 × 5 factorial arrangement, and three replications was used. The treatments consisted of six grain sorghum varieties (1011-IPA, 2502-IPA, 2564-IPA, 2600-IPA, Ponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
5
7
0
3
Order By: Relevance
“…Guimarães et al [66] found a 50% WUE decline with an EC w of 6.9 dS m −1 in sorghum, in accordance with the sharp WUE decrease observed in our experiment (Figure 3D). Richardson and McCree [67] and Yan et al [68] argued that sorghum reduces stomatal conductance and transpiration under salinity, potentially leading to WUE increases.…”
Section: Discussionsupporting
confidence: 92%
“…Guimarães et al [66] found a 50% WUE decline with an EC w of 6.9 dS m −1 in sorghum, in accordance with the sharp WUE decrease observed in our experiment (Figure 3D). Richardson and McCree [67] and Yan et al [68] argued that sorghum reduces stomatal conductance and transpiration under salinity, potentially leading to WUE increases.…”
Section: Discussionsupporting
confidence: 92%
“…Poucas variáveis de crescimento e de acúmulo de matéria seca do sorgo foram afetadas pelos distintos regimes hídricos (Tabelas I e II). Este resultado pode estar associado à alta tolerância do sorgo à seca e ao excesso de água combinados ao estresse salino (Guimarães et al, 2016;Guimarães et al, 2019). Nestas condições, o sorgo limita as suas atividades metabólicas (Bell et al, 2015).…”
Section: Discussionunclassified
“…O sorgo possui características fisiológicas que permitem interromper o crescimento ou limitar as suas atividades metabólicas sob escassez hídrica (Bell et al, 2015;Guimarães et al, 2019). Por outro lado, as plantas sujeitas ao excesso hídrico possuem sua condutância estomática afetada e diminui as taxas de fotossíntese e de crescimento, ocasionando em queda da produção da parte aérea e de raízes.…”
Section: Introductionunclassified
“…Salinity is one of the most severe environmental stresses and the responses given by plants are diverse. These are reflected in physiological variables (stomach conductance, rate of perspiration and photosynthesis) (Freire et al, 2014), biometrics (height, leaf area, biomass production) (Guimarães et al, 2019), biochemistry (antioxidant enzymes) (Barbosa et al, 2014). Sorghum bicolor (L.) Moench is a crop species that presents C4 mechanism, and is one of the most versatile and efficient species in terms of photosynthetic mechanism (Berenguer & Faci, 2001).…”
Section: Introductionmentioning
confidence: 99%